AMELIORATIVE EFFECTS OF MELATONIN AGAINST 2,4-DICHLOROPHENOXYACETIC ACID TOXICITY IN KIDNEY OF MICE – A HISTOLOGICAL STUDY. - Upadhyaya, Ashlesh M; Rao, Mandava V; Jhala, Devendrasinh D (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The compound, 2,4-dichlorophenoxyacetic acid (2,4-D), is a systemic phenoxy herbicide and a plant growth regulator. Histopathological effects of 2,4-D alone and in combination with melatonin on the kidney in adult albino male mice of the Swiss strain were evaluated in the present study. Methods: Twenty adult male albino mice weighing between 30 and 40 g were assigned into four groups with five mice in each group. Group I served as control; Group II - melatonin alone (10 mg/kg body weight); Group III - 2,4-D alone (50 mg/kg body weight); and Group IV - 2,4-D + melatonin was given orally for 45 days. Results: It revealed a significant reduction in the body and kidney weights (p<0.001 and p<0.01 respectively) of mice treated with 2,4-D, while the body and kidney weights after treatment of melatonin and 2,4-D + melatonin were comparable to control. Histological study revealed that 2,4-D induced nephrotoxicity evidenced by various histological changes including shrinkage of the glomerulus, tubular dilation, hypertrophy of tubular epithelium, and degeneration of renal tubules. Conclusion: Treating animals with the melatonin along with 2,4-D showed mitigative effects of melatonin and minimized the structural alteration in the kidney of mice appeared due to 2,4-D toxicity.